The Entrepreneurial Logic: Effectuation and Cooperation (Global Journal of Management and Business Research, 2024)
Considering that entrepreneurship has been consolidated in Brazil and around the world, it is essential to understand how decisions to undertake have been made in the face of competitive evolution. This work aims to understand the entrepreneurial logic of effectuation for the development of cooperation as a strategy for adding value and competitive advantage. In this way, the present work seeks to present theories about the logic of effectuation and cooperation to relate them to the entrepreneurial action presented in the Global Entrepreneurship Monitor survey (GEM), 2022. The methodological approach of the research was qualitative, field and bibliographical; it enabled the concepts studied to be identified and analyzed. A census was conducted with entrepreneurs located in a food truck plaza in Parque das Laranjeiras neighborhood, in Manaus, Brazil. Perceived as an original gap, this absence inspired the writing of this article. To this end, we adopted a mixed-methods approach and exploratory-descriptive research. The results identified show that entrepreneurs use the effectuation logic, valuing their entrepreneurial action characteristics.
Keywords: entrepreneurship; effectuation logic; cooperation; strategy; GEM survey